Surface Solid Dispersion and Solid Dispersion of Meloxicam: Comparison and Product Development - Mayank Chaturvedi; Manish Kumar; Kamla Pathak; Shailendra Bhatt; Vipin Saini (Tabriz University of Medical Sciences, 2017)
Purpose: A comparative study was carried out between surface solid dispersion (SSD) and solid dispersion (SD) of meloxicam (MLX) to assess the solubility and dissolution enhancement approach and thereafter develop as patient friendly orodispersible tablet. Methods: Crospovidone (CPV), a hydrophilic carrier was selected for SSD preparation on the basis of 89% in- vitro MLX adsorption, 19% hydration capacity and high swelling index. SD on the other hand was made with PEG4000. Both were prepared by co-grinding and solvent evaporation method using drug: carrier ratios of 1:1, 1:4, and 1:8. Formulation SSDS3 (MLX: CPV in 1:8 ratio) made by solvent evaporation method showed t50% of 28 min and 80.9% DE50min which was higher in comparison to the corresponding solid dispersion, SDS3 (t50% of 35min and 76.4% DE50min). Both SSDS3 and SDS3 were developed as orodispersible tablets and evaluated. Results: Tablet formulation F3 made with SSD3 with a disintegration time of 11 secs, by wetting time= 6 sec, high water absorption of 78%by wt and cumulative drug release of 97% proved to be superior than the tablet made with SD3. Conclusion: Conclusively, the SSD of meloxicam has the potential to be developed as fast acing formulation that can ensure almost complete release of drug.